(untitled) (LIS TODAY, 2023)
The study investigated the extent to which organizational politics affected job performance of librarians in Ahmadu Bello University (ABU), Zaria. The study adopted survey research design. Population of the study consisted of 162 librarians from ABU library, Zaria. There was no sampling technique involved in this study because the researcher is interested in the total population, therefore total enumeration or census method was adopted for this study. This is because the researcher considered the population as not too large to manage and that the use of the total enumeration can eliminate any potential bias that may occur if a sample is selected and allowed for the generalization of the findings from the study. The researcher employed the questionnaire as the research instrument for collecting data in this study.162 questionnaires were distributed to the respondents, out of which 132 (88,8%) were returned. The data collected was analyzed by using Statistical Package for Social Science (SPSS) version 21. The data collected was analyzed using descriptive statistics such as frequency distribution, percentages, mean and standard deviation. The findings revealed that the level of librarians’ job performance ABU, Zaria library was high (Average Weighted Mean = 3.30), on a scale of 4. Job performance was measured by three indicators (declarative knowledge, motivation and procedural knowledge). The finding also of revealed that the organizational politics takes place among the librarians in ABU library in Zaria (Average Weighted Mean = 3.09). The study concluded that organizational politics contributed to librarians’ job performance in ABU Zaria. The study recommended that the level of librarians’ job performance in ABU Zaria should be sustained by library management.